A Critical Review of the Book Al-Udab al-Maqarran Fei Persia and Al-Alam al-Arabi - Sabereh Siavashi; Maryam Alipoor (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Studying academic and academic books often aims at transforming the quality of education in order to reveal the angles that are hidden from the author’s point of view. One of the books published in the field of comparative literature developed for undergraduate Arabic language and literature students is the book Aladb al-Moghrannfi Iran and Al-Alam al-Arabi (1903-2012) by Heydar Khezri, published by Sindi Publications. This book is important because it introduces new schools of comparative literature and examines them. Hence, this study examines the book in two parts of the form and content and examines the privileges and drawbacks in each section. Among the results are: Although the author has written his first work in this field, the book has a good coherence, so that the reader is well versed in the study of the book with comparative literature, especially in the field of two Persian and Arabic Literature. In addition, the noteworthy mention of the book is that this work has taken a new step in identifying new schools and theories in the field of comparative literature than other works written in this field, while avoiding repeated repetition, innovation has struck.